The role of elevated red blood cell distribution width in the prognosis of AECOPD patients: A retrospective study. Issue 10 (12th March 2021) - Zhu, Mengpei; Peng, Hongxing; Wan, Lei; Zhang, Shuling; Zeng, Yulan
Abstract : Abstract: Chronic obstructive pulmonary disease (COPD) is still a constant threat to people's health. We aimed to identify the relationship between increased red cell distribution width (RDW) on admission and length of hospitalization in acute exacerbation of chronic obstructive pulmonary disease patients (AECOPD). Patients with AECOPD were recruited and divided into 3 groups based on RDW tertiles. Two hundred eighty six patients with AECOPD admitted to our department during January 1, 2017 and June 30, 2019 were enrolled in the study. According to the RDW tertiles (⩽12.8%, 12.9% to 13.6%, >13.6%), the patients were divided into 3 groups. Length of stay was significantly related to RDW ( P  < .001) in AECOPD patients. Correlation analysis indicated that RDW was negatively associated with FEV1% predicted ( r  = −0.142, P  = .016). However, RDW was positively associated with prolonged of stay ( r  = 0.298, P  < .001) in AECOPD patients. Multivariate regression analysis discovered that RDW was independently associated with the length of hospitalization ( P  = .001). Receiver operating characteristic (ROC) curve showed that RDW was a good predictor of prolonged hospital stay in AECOPD patients, and the area under the curve (AUC) was 0.818 (95% CI: 0.769–0.868). The highest sensitivity to predict prolonged hospital stay was 83.8% and the specificity was 71.6% with the cut-off 13.35%. In conclusion, prolonged hospital stay in AECOPD patients was closely associated with increased RDW. Elevated RDW may be an independent predictor for prolonged hospitalization in AECOPD patients.